KNOWLEDGE MANAGEMENT AS A STRATEGIC BUSINESS RESOURCE - Ghiorghita, Eugen; Grzegorczyk, Adam (Journal of Economic Development, Environment and People, 2017)
The development of a knowledge-based economy means that today’s businesses face many of the new challenges of adapting to the changing environment. Since the early 1990s, knowledge management became not only an academic discipline, but more than that, an effective way to assure the continuous improvement of the organization. The search for competitive advantages led companies to focus on the complex philosophy of intellectual capital and its connected concepts: human capital, structural capital, organizational capital, intellectual property, and last but not least, relational capital. The present article puts forward a short insight into the complexity of the ever changing and evolving system of knowledge management various concepts.